Comparison Effects of Propofol-Dexmedetomidine versus Propofol-Remifentanil for Endoscopic Ultrasonography: A Prospective Randomized Comparative Trial. (7th November 2022) - Zhao, Liang; Zhang, Yonglai; Xu, Shoucai; Wang, Xiuqin
Abstract : Objective. To compare the effects of propofol-dexmedetomidine versus propofol-remifentanil for endoscopic ultrasonography (EUS). Design, Setting, and Participants. A single-center, randomized trial from August 20, 2020 to August 20, 2021, in patients undergoing EUS. Interventions. Propofol-dexmedetomidine (PD) versus propofol-remifentanil (PR). Outcome Measures. The primary outcome was the endoscopist satisfaction level. The secondary outcomes included patient satisfaction, the incidence of adverse events, induction time, and time to achieve postanesthesia discharge score (PADS) ≥9. Methods. Total of 200 patients were enrolled and randomized into PD and PR groups. A bolus dose of 0.5 μ g/kg dexmedetomidine was injected intravenously for 5 min. Subsequently, a continuous infusion of 0.5 μ g/kg/h for the PD group. Remifentanil was continuously infused at 1.5 μ g/kg/h for the PR group. A bolus dose of 1 mg/kg propofol was administered to both groups and then continuously infused. Results. The endoscopist satisfaction level was higher in the PR group than in the PD group (P = 0.009 ). Patient satisfaction was not significantly different between the groups (P = 0.738 ). No patients required mask ventilation or tracheal intubation in both groups. All patients were relatively hemodynamically stable. The incidence of body movements during the procedure in the PD group was higher than in the PR group (P = 0.035 ). The induction time and time taken to achieve PADS ≥9 in the PD group were longer than in the PR group (P < 0.05 ). Conclusions. PR sedation can increase the satisfaction level of the endoscopist by providing faster induction time and lower body movement and that of the patient by achieving faster PADS than PD sedation. Trial registration number: http://www.chictr.org.cn (ChiCTR2000034987 ).